Prevalência de lesões do músculo elevador do ânus em mulheres primíparas após parto e a sua influência nas disfunções do pavimento pélvico: implicações para a fisioterapia (revisão sistemática) - Pessoa, Patrícia de Barros (2022)
Introduction: The levator ani muscle (LAM) is the main muscle of the pelvic floor and studies show a significant association between injuries of the LAM and the first vaginal delivery, which can cause pelvic floor disorders (PFDs). This study aims to identify the prevalence of short and long-term LAM injuries after vaginal delivery in primiparous women and its influence on PFDs. Additionally, this study, it is further intended to discuss the role of physical therapy in the recovery of PFDs. Methodology: A systematic review was conducted according to the PRISMA methodology. The databases used were Pubmed, Cochrane, and PEDro. The quality assessment of the evidence was carried out using the Critical Appraisal Skills Programme (CASP). Both the selection of studies and their evaluation were done by two researchers, and by a third reviewer in cases of disagreement. Data were collected on samples, assessment tools, moments of the assessments, and main results. Results: From the search were gathered 57 articles in total, 19 of which were included for matching the eligibility criteria. The prevalence of avulsion of the LAM was found in association with vaginal delivery between 18% and 25%, more often on the right side. Ballooning was detected in 20% to 37% of women, appearing to be more common when compared to avulsion. Pelvic organ prolapse (POP) was considered the most common disorder associated with injuries of the LAM and there seems to be some connection with sexual dysfunction. An association between urinary incontinence (UI) and anal incontinence (AI) was not sufficiently supported by the studies included. Conclusion: Avulsion of the LAM and ballooning of the hiatal area have a high prevalence in primiparous women after vaginal delivery and have a strong direct relation to the development of POP.